Effect of the Specimen’s Height on the Split-Tensile Strength of the Fibers Reinforced Clay-Lime-Rice Husk Ask Mixture - Hartono, Edi; Muntohar, Agus Setyo; Diana, Willis; Hemeto, Abd. Dzargifar (Journal of the Civil Engineering Forum, 2024)
Various studies on the effect of specimen size on splitting tensile strength. However, geotechnical codes lack consensus regarding the recommended specimen diameter and height-to-diameter (H/D) ratio for the split tensile strength test. Hence, it is imperative to study the effect of the height-to-diameter ratio of the specimen on the outcomes of the split tensile strength test, especially for stabilized and fiber-reinforced soil. This research examines the effect of adding lime-rice husk ash and plastic fiber and the effect of specimen size on splitting tensile strength. The height of the specimen is varied, using a height-to-diameter ratio (H/D), namely 0.5, 1.0, 1.5, 2.0, and 2.5, in which the diameter is 70 mm. Two groups of specimens were prepared as stabilized clay without fibers and stabilized clay with 0.1% fibers. The lime required for stabilization is 10% of the dry weight of the soil. In this research, the lime and rice husk ash ratio was designed as 1:1. The splitting tensile strength test was carried out after the specimen was cured for seven days. The investigation indicates that the splitting tensile strength of the specimen without fibers reduces from 217 kPa to 150 kPa as the H/D ratio grows from 0.5 to 2.5. Conversely, the tensile strength of the specimen with fibers increases from 284 kPa to 357 kPa. The findings suggest that the fiber inclusion enhances the splitting tensile strength of the stabilized clay. The specimen size affects the splitting tensile strength, but the effect becomes less noticeable when the H/D ratio exceeds 2.5. From a fracture mechanism perspective, the specimen experiences mode II (shearing) due toa probable “flexural action” along its height. It remains challenging to conclude the dimensions of the test specimen or, at the very least, estimate the correction factor for the size-to-tensile strength ratio.